CDC ROADM design tradeoffs due to physical layer impairments in optical networks - Sequeira, D. G. (2022)
In this work, we assess the impact of several physical layer impairments (PLIs) on the performance of optical networks based on colorless, directionless and contentionless reconfigurable optical add/drop multiplexers (ROADMs), through Monte-Carlo simulation, and considering polarization division multiplexing 4 and 16 quadrature amplitude modulation (QAM) signals, at 28 GBaud, for 37.5 GHz optical channels. The PLIs taken into account are the amplified spontaneous emission noise, optical filtering, in-band crosstalk and nonlinear interference noise caused by Kerr effect. A detailed model of the ROADM node is built considering two typical ROADM architectures, broadcast and select (B&S) and route and select (R&S), and two different add/drop structures, multicast switches (MCSs) and wavelength selective switches (WSSs), resulting in four different ROADM node scenarios. Our results have shown that for 16QAM signals, the B&S ROADMs with WSSs-based add/drop structures is the scenario that has the best relation cost/performance, foreseeing its use in metro networks, while for 4QAM signals, the R&S ROADM with WSSs-based add/drop structure scenario allows a larger ROADM cascade at an expectable lower cost anticipating its implementation in long-haul networks.